A new proof of Lucas’ Theorem

Alexandre Laugier Lycée professionnel hotelier La Closerie, 10 rue Pierre Loti - BP 4, 22410 Saint-Quay-Portrieux, France laugier.alexandre@orange.fr  and  Manjil P. Saikia Department of Mathematical Sciences, Tezpur University, Napaam, Sonitpur, Assam, Pin-784028, India manjil@gonitsora.com
Abstract.

We give a new proof of Lucas’ Theorem in elementary number theory.

The second author is supported by DST INSPIRE Scholarship 422/2009 from Department of Science and Technology, Government of India.

Key Words:Lucas’ theorem.

2010 Mathematical Reviews Classification Numbers: 11A07, 11A41, 11A51, 11B50, 11B65, 11B75.

1. Introduction

One of the most useful results in elementary number theory is the following result of E. Lucas

Theorem 1.1 ([1],E. Lucas (1878)).

Let p𝑝p be a prime and m𝑚m and n𝑛n be two integers considered in the following way,

m=akpk+ak1pk1++a1p+a0,𝑚subscript𝑎𝑘superscript𝑝𝑘subscript𝑎𝑘1superscript𝑝𝑘1subscript𝑎1𝑝subscript𝑎0m=a_{k}p^{k}+a_{k-1}p^{k-1}+\ldots+a_{1}p+a_{0},
n=blpl+bl1pl1++b1p+b0,𝑛subscript𝑏𝑙superscript𝑝𝑙subscript𝑏𝑙1superscript𝑝𝑙1subscript𝑏1𝑝subscript𝑏0n=b_{l}p^{l}+b_{l-1}p^{l-1}+\ldots+b_{1}p+b_{0},

where all aisubscript𝑎𝑖a_{i} and bjsubscript𝑏𝑗b_{j} are non-negative integers less than p𝑝p. Then,

(mn)=(akpk+ak1pk1++a1p+a0blpl+bl1pl1++b1p+b0)i=0max(k,l)(aibi)(modp).binomial𝑚𝑛binomialsubscript𝑎𝑘superscript𝑝𝑘subscript𝑎𝑘1superscript𝑝𝑘1subscript𝑎1𝑝subscript𝑎0subscript𝑏𝑙superscript𝑝𝑙subscript𝑏𝑙1superscript𝑝𝑙1subscript𝑏1𝑝subscript𝑏0superscriptsubscriptproduct𝑖0𝑘𝑙binomialsubscript𝑎𝑖subscript𝑏𝑖mod𝑝\binom{m}{n}=\binom{a_{k}p^{k}+a_{k-1}p^{k-1}+\ldots+a_{1}p+a_{0}}{b_{l}p^{l}+b_{l-1}p^{l-1}+\ldots+b_{1}p+b_{0}}\equiv\prod_{i=0}^{\max(k,l)}\binom{a_{i}}{b_{i}}~{}(\textup{{mod}}~{}p).

Notice that the theorem is true if aibisubscript𝑎𝑖subscript𝑏𝑖a_{i}\geq b_{i} for i=0,1,2,,max(k,l)𝑖012𝑘𝑙i=0,1,2,\ldots,\max(k,l)

There has been many different proofs of this result in the years that followed its first publication. We present here an alternate approach using elementary number theoretic techniques.

2. Proof of Theorem 1.1

First of all, we state and prove a few lemmas

Lemma 2.1.

If

a0+a1X+a2X2++anXnb0+b1X+b2X2++bnXn(modp)subscript𝑎0subscript𝑎1𝑋subscript𝑎2superscript𝑋2subscript𝑎𝑛superscript𝑋𝑛subscript𝑏0subscript𝑏1𝑋subscript𝑏2superscript𝑋2subscript𝑏𝑛superscript𝑋𝑛mod𝑝a_{0}+a_{1}X+a_{2}X^{2}+\ldots+a_{n}X^{n}\equiv b_{0}+b_{1}X+b_{2}X^{2}+\ldots+b_{n}X^{n}~{}(\textup{mod}~{}p)

then

aibi(modp)i[[0,n]].subscript𝑎𝑖subscript𝑏𝑖mod𝑝for-all𝑖delimited-[]0𝑛a_{i}\equiv b_{i}~{}(\textup{mod}~{}p)\,\,\forall\,i\in[[0,n]].
Proof.

Indeed, if a0+a1X+a2X2++anXnb0+b1X+b2X2++bnXn(modp)subscript𝑎0subscript𝑎1𝑋subscript𝑎2superscript𝑋2subscript𝑎𝑛superscript𝑋𝑛subscript𝑏0subscript𝑏1𝑋subscript𝑏2superscript𝑋2subscript𝑏𝑛superscript𝑋𝑛mod𝑝a_{0}+a_{1}X+a_{2}X^{2}+\cdots+a_{n}X^{n}\equiv b_{0}+b_{1}X+b_{2}X^{2}+\cdots+b_{n}X^{n}~{}(\textup{mod}~{}p), then there exits a polynomial k(X)=k0+k1X+k2X2++knXn𝑘𝑋subscript𝑘0subscript𝑘1𝑋subscript𝑘2superscript𝑋2subscript𝑘𝑛superscript𝑋𝑛k(X)=k_{0}+k_{1}X+k_{2}X^{2}+\cdots+k_{n}X^{n} at most of degree n𝑛n such that a0+a1X+a2X2++anXn=b0+b1X+b2X2++bnXn+p(k0+k1X+k2X2++knXn)subscript𝑎0subscript𝑎1𝑋subscript𝑎2superscript𝑋2subscript𝑎𝑛superscript𝑋𝑛subscript𝑏0subscript𝑏1𝑋subscript𝑏2superscript𝑋2subscript𝑏𝑛superscript𝑋𝑛𝑝subscript𝑘0subscript𝑘1𝑋subscript𝑘2superscript𝑋2subscript𝑘𝑛superscript𝑋𝑛a_{0}+a_{1}X+a_{2}X^{2}+\cdots+a_{n}X^{n}=b_{0}+b_{1}X+b_{2}X^{2}+\cdots+b_{n}X^{n}+p(k_{0}+k_{1}X+k_{2}X^{2}+\cdots+k_{n}X^{n}). This gives a0+a1X+a2X2++anXn=b0+pk0+(b1+pk1)X+(b2+pk2)X2++(bn+pkn)Xnsubscript𝑎0subscript𝑎1𝑋subscript𝑎2superscript𝑋2subscript𝑎𝑛superscript𝑋𝑛subscript𝑏0𝑝subscript𝑘0subscript𝑏1𝑝subscript𝑘1𝑋subscript𝑏2𝑝subscript𝑘2superscript𝑋2subscript𝑏𝑛𝑝subscript𝑘𝑛superscript𝑋𝑛a_{0}+a_{1}X+a_{2}X^{2}+\cdots+a_{n}X^{n}=b_{0}+pk_{0}+(b_{1}+pk_{1})X+(b_{2}+pk_{2})X^{2}+\cdots+(b_{n}+pk_{n})X^{n}. Hence we get a0=b0+pk0subscript𝑎0subscript𝑏0𝑝subscript𝑘0a_{0}=b_{0}+pk_{0}, a1=b1+pk1subscript𝑎1subscript𝑏1𝑝subscript𝑘1a_{1}=b_{1}+pk_{1}, a2=b2+pk2subscript𝑎2subscript𝑏2𝑝subscript𝑘2a_{2}=b_{2}+pk_{2} ,…, an=bn+pknsubscript𝑎𝑛subscript𝑏𝑛𝑝subscript𝑘𝑛a_{n}=b_{n}+pk_{n}. Or equivalently a0b0(modp)subscript𝑎0subscript𝑏0mod𝑝a_{0}\equiv b_{0}~{}(\textup{mod}~{}p), a1=b1(modp)subscript𝑎1subscript𝑏1mod𝑝a_{1}=b_{1}~{}(\textup{mod}~{}p), a2=b2(modp)subscript𝑎2subscript𝑏2mod𝑝a_{2}=b_{2}~{}(\textup{mod}~{}p) ,\cdots, an=bn(modp)subscript𝑎𝑛subscript𝑏𝑛mod𝑝a_{n}=b_{n}~{}(\textup{mod}~{}p).

The reciprocal implication is trivial. ∎

Lemma 2.2.

If the base p𝑝p expansion of a positive integer n𝑛n is,

n=a0+a1p+a2p2++alpl𝑛subscript𝑎0subscript𝑎1𝑝subscript𝑎2superscript𝑝2subscript𝑎𝑙superscript𝑝𝑙n=a_{0}+a_{1}p+a_{2}p^{2}+\cdots+a_{l}p^{l}

then we have

n!=qa0!(a1p)!(a2p2)!(alpl)!𝑛𝑞subscript𝑎0subscript𝑎1𝑝subscript𝑎2superscript𝑝2subscript𝑎𝑙superscript𝑝𝑙n!=qa_{0}!(a_{1}p)!(a_{2}p^{2})!\cdots(a_{l}p^{l})!

with q𝑞q a natural number.

Proof.

Since the factorial of a natural number is a natural number, there exists a rational number q such that

q=n!a0!(a1p)!(a2p2)!(alpl)!.𝑞𝑛subscript𝑎0subscript𝑎1𝑝subscript𝑎2superscript𝑝2subscript𝑎𝑙superscript𝑝𝑙q=\frac{n!}{a_{0}!(a_{1}p)!(a_{2}p^{2})!\ldots(a_{l}p^{l})!}.

Let S𝑆S be the set,

S={x1,x2,,xl}.𝑆subscript𝑥1subscript𝑥2subscript𝑥𝑙S=\left\{x_{1},x_{2},\ldots,x_{l}\right\}.

We consider lists of elements of S𝑆S where x0subscript𝑥0x_{0} is repeated a0subscript𝑎0a_{0} times, x1subscript𝑥1x_{1} is repeated a1psubscript𝑎1𝑝a_{1}p times,\ldots, xlsubscript𝑥𝑙x_{l} is repeated alplsubscript𝑎𝑙superscript𝑝𝑙a_{l}p^{l} times such that, 0aip10subscript𝑎𝑖𝑝10\leq a_{i}\leq p-1 with i[[0,l]]𝑖delimited-[]0𝑙i\in[[0,l]]. In such a list, there are l+1𝑙1l+1 unlike groups of identical elements. For instance the selection (x0,x0,,x0a0,x1,x1,,x1a1p,,xl,xl,,xlalpl)subscriptsubscript𝑥0subscript𝑥0subscript𝑥0subscript𝑎0subscriptsubscript𝑥1subscript𝑥1subscript𝑥1subscript𝑎1𝑝subscriptsubscript𝑥𝑙subscript𝑥𝑙subscript𝑥𝑙subscript𝑎𝑙superscript𝑝𝑙\left(\underbrace{x_{0},x_{0},\ldots,x_{0}}_{a_{0}},\underbrace{x_{1},x_{1},\ldots,x_{1}}_{a_{1}p},\ldots\ldots,\underbrace{x_{l},x_{l},\ldots,x_{l}}_{a_{l}p^{l}}\right) is such a list of n𝑛n elements which contains l+1𝑙1l+1 unlike groups of identical elements.

The number of these lists is given by n!a0!(a1p)!(a2p2)!(alpl)!𝑛subscript𝑎0subscript𝑎1𝑝subscript𝑎2superscript𝑝2subscript𝑎𝑙superscript𝑝𝑙\frac{n!}{a_{0}!(a_{1}p)!(a_{2}p^{2})!\ldots(a_{l}p^{l})!}. It proves that the rational number q𝑞q is a natural number. And, since the factorial of a natural number is non-zero (even if this number is 00 because 0!=1010!=1), we deduce that q𝑞q is a non-zero natural number. ∎

Theorem 2.3.

Let n=ap+b=a0+a1p+a2p2++alpl𝑛𝑎𝑝𝑏subscript𝑎0subscript𝑎1𝑝subscript𝑎2superscript𝑝2subscript𝑎𝑙superscript𝑝𝑙n=ap+b=a_{0}+a_{1}p+a_{2}p^{2}+\ldots+a_{l}p^{l} such that 0bp10𝑏𝑝10\leq b\leq p-1 and 0aip10subscript𝑎𝑖𝑝10\leq a_{i}\leq p-1 with i[[0,l]]𝑖delimited-[]0𝑙i\in[[0,l]]. Then q1(modp)𝑞1mod𝑝q\equiv 1~{}(\textup{mod}~{}p).

Before we prove Theorem 2.3 we shall state and prove the following non-trivial lemmas.

Lemma 2.4.

The integers q𝑞q and p𝑝p are relatively prime.

Proof.

If 0<q<p0𝑞𝑝0<q<p, since p𝑝p is prime, q𝑞q and p𝑝p are relatively prime.

If qp𝑞𝑝q\geq p, let us assume that p𝑝p and q𝑞q are not relatively prime. It would imply that there exist an integer x>0𝑥0x>0 and a non-zero natural number qsuperscript𝑞q^{\prime} such that q=qpx𝑞superscript𝑞superscript𝑝𝑥q=q^{\prime}p^{x} with gcd(q,p)=1gcdsuperscript𝑞𝑝1\textup{gcd}(q^{\prime},p)=1. Since n!=qa0!(a1p)!(al1pl1)!(alpl)!𝑛𝑞subscript𝑎0subscript𝑎1𝑝subscript𝑎𝑙1superscript𝑝𝑙1subscript𝑎𝑙superscript𝑝𝑙n!=qa_{0}!(a_{1}p)!\ldots(a_{l-1}p^{l-1})!(a_{l}p^{l})! we get n!=qpxa0!(a1p)!(alpl)!𝑛superscript𝑞superscript𝑝𝑥subscript𝑎0subscript𝑎1𝑝subscript𝑎𝑙superscript𝑝𝑙n!=q^{\prime}p^{x}a_{0}!(a_{1}p)!\ldots(a_{l}p^{l})!. It follows that n!𝑛n! would contain a factor al+xpl+xsubscript𝑎𝑙𝑥superscript𝑝𝑙𝑥a_{l+x}p^{l+x} such that q=al+xq′′superscript𝑞subscript𝑎𝑙𝑥superscript𝑞′′q^{\prime}=a_{l+x}q^{\prime\prime} with al+x[[1,p1]]subscript𝑎𝑙𝑥delimited-[]1𝑝1a_{l+x}\in[[1,p-1]]. But, al+xpl+x>nsubscript𝑎𝑙𝑥superscript𝑝𝑙𝑥𝑛a_{l+x}p^{l+x}>n.

Indeed we know that 1+p++pl=pl+11p11𝑝superscript𝑝𝑙superscript𝑝𝑙11𝑝11+p+\ldots+p^{l}=\frac{p^{l+1}-1}{p-1}. So pl+1=1+(p1)(1+p++pl)superscript𝑝𝑙11𝑝11𝑝superscript𝑝𝑙p^{l+1}=1+(p-1)(1+p+\ldots+p^{l}). Then pl+1>(p1)+(p1)p++(p1)plsuperscript𝑝𝑙1𝑝1𝑝1𝑝𝑝1superscript𝑝𝑙p^{l+1}>(p-1)+(p-1)p+\ldots+(p-1)p^{l}. Since 0aip10subscript𝑎𝑖𝑝10\leq a_{i}\leq p-1 with i[[0,l]]𝑖delimited-[]0𝑙i\in[[0,l]], we have 0aipi(p1)pi0subscript𝑎𝑖superscript𝑝𝑖𝑝1superscript𝑝𝑖0\leq a_{i}p^{i}\leq(p-1)p^{i} with i[[0,l]]𝑖delimited-[]0𝑙i\in[[0,l]]. Therefore, pl+1>a0+a1p++alplsuperscript𝑝𝑙1subscript𝑎0subscript𝑎1𝑝subscript𝑎𝑙superscript𝑝𝑙p^{l+1}>a_{0}+a_{1}p+\ldots+a_{l}p^{l} so pl+1>nal+xpl+x>nsuperscript𝑝𝑙1𝑛subscript𝑎𝑙𝑥superscript𝑝𝑙𝑥𝑛p^{l+1}>n\,\Rightarrow\,a_{l+x}p^{l+x}>n.

Since n!𝑛n! doesn’t include terms like al+xpl+x>nsubscript𝑎𝑙𝑥superscript𝑝𝑙𝑥𝑛a_{l+x}p^{l+x}>n with al+x[[1,p1]]subscript𝑎𝑙𝑥delimited-[]1𝑝1a_{l+x}\in[[1,p-1]], we obtain a contradiction. It means that the assumption q=qpx𝑞superscript𝑞superscript𝑝𝑥q=q^{\prime}p^{x} with x𝑥superscriptx\in\mathbb{N}^{\star} and gcd(q,p)=1𝑔𝑐𝑑superscript𝑞𝑝1gcd(q^{\prime},p)=1 is not correct. So, q𝑞q is not divisible by a power of p𝑝p. It results that q𝑞q and p𝑝p are relatively prime. ∎

We know that n!=(ap+b)!=qa0!(a1p)!(alpl)!𝑛𝑎𝑝𝑏𝑞subscript𝑎0subscript𝑎1𝑝subscript𝑎𝑙superscript𝑝𝑙n!=(ap+b)!=qa_{0}!(a_{1}p)!\ldots(a_{l}p^{l})! with a=np𝑎𝑛𝑝a=\lfloor\frac{n}{p}\rfloor, 0aip10subscript𝑎𝑖𝑝10\leq a_{i}\leq p-1 with i=0,1,2,,p1𝑖012𝑝1i=0,1,2,\ldots,p-1 and b=a0𝑏subscript𝑎0b=a_{0}. Let qa,l,1,isubscript𝑞𝑎𝑙1𝑖q_{a,l,1,i} with 0ia1a0𝑖subscript𝑎1𝑎0\leq i\leq a_{1}\leq a be the natural number

qa,l,1,i=(ap+bip)!a0!((a1i)p)!(a2p2)!(alpl)!.subscript𝑞𝑎𝑙1𝑖𝑎𝑝𝑏𝑖𝑝subscript𝑎0subscript𝑎1𝑖𝑝subscript𝑎2superscript𝑝2subscript𝑎𝑙superscript𝑝𝑙q_{a,l,1,i}=\frac{(ap+b-ip)!}{a_{0}!((a_{1}-i)p)!(a_{2}p^{2})!\ldots(a_{l}p^{l})!}.

In particular, we have q=qa,l,1,0𝑞subscript𝑞𝑎𝑙10q=q_{a,l,1,0}.

Lemma 2.5.

qa,l,1,i+1qa,l,1,i(modp).subscript𝑞𝑎𝑙1𝑖1subscript𝑞𝑎𝑙1𝑖mod𝑝q_{a,l,1,i+1}\equiv q_{a,l,1,i}~{}(\textup{mod}~{}p).

Proof.

We have (0i<a10𝑖subscript𝑎10\leq i<a_{1})

(ap+bipp)=qa,l,1,iqa,l,1,i+1((a1i)pp)binomial𝑎𝑝𝑏𝑖𝑝𝑝subscript𝑞𝑎𝑙1𝑖subscript𝑞𝑎𝑙1𝑖1binomialsubscript𝑎1𝑖𝑝𝑝{ap+b-ip\choose p}=\frac{q_{a,l,1,i}}{q_{a,l,1,i+1}}{(a_{1}-i)p\choose p}

Or equivalently

qa,l,1,i+1(ap+bipp)=qa,l,1,i((a1i)pp).subscript𝑞𝑎𝑙1𝑖1binomial𝑎𝑝𝑏𝑖𝑝𝑝subscript𝑞𝑎𝑙1𝑖binomialsubscript𝑎1𝑖𝑝𝑝q_{a,l,1,i+1}{ap+b-ip\choose p}=q_{a,l,1,i}{(a_{1}-i)p\choose p}.

Now

(ap+bipp)=((ai)p+bp)aia1i(modp),binomial𝑎𝑝𝑏𝑖𝑝𝑝binomial𝑎𝑖𝑝𝑏𝑝𝑎𝑖subscript𝑎1𝑖mod𝑝{ap+b-ip\choose p}={(a-i)p+b\choose p}\equiv a-i\equiv a_{1}-i~{}(\textup{mod}~{}p),

and

((a1i)pp)a1i(modp).binomialsubscript𝑎1𝑖𝑝𝑝subscript𝑎1𝑖mod𝑝{(a_{1}-i)p\choose p}\equiv a_{1}-i~{}(\textup{mod}~{}p).

Therefore

qa,l,1,i+1(a1i)qa,l,1,i(a1i)(modp).subscript𝑞𝑎𝑙1𝑖1subscript𝑎1𝑖subscript𝑞𝑎𝑙1𝑖subscript𝑎1𝑖mod𝑝q_{a,l,1,i+1}(a_{1}-i)\equiv q_{a,l,1,i}(a_{1}-i)~{}(\textup{mod}~{}p).

Since a1isubscript𝑎1𝑖a_{1}-i with i=0,1,2,,a11𝑖012subscript𝑎11i=0,1,2,\ldots,a_{1}-1 and p𝑝p are relatively prime, so qa,l,1,i+1qa,l,1,i(modp)subscript𝑞𝑎𝑙1𝑖1subscript𝑞𝑎𝑙1𝑖mod𝑝q_{a,l,1,i+1}\equiv q_{a,l,1,i}~{}(\textup{mod}~{}p). ∎

Notice that qa,l,1,a1subscript𝑞𝑎𝑙1subscript𝑎1q_{a,l,1,a_{1}} corresponds to the case where a1=0subscript𝑎10a_{1}=0, (a0+a2p2++alpl)!=qa,l,1,a1a0!(a2p2)!(alpl)!subscript𝑎0subscript𝑎2superscript𝑝2subscript𝑎𝑙superscript𝑝𝑙subscript𝑞𝑎𝑙1subscript𝑎1subscript𝑎0subscript𝑎2superscript𝑝2subscript𝑎𝑙superscript𝑝𝑙(a_{0}+a_{2}p^{2}+\ldots+a_{l}p^{l})!=q_{a,l,1,a_{1}}a_{0}!(a_{2}p^{2})!\ldots(a_{l}p^{l})!.

Lemma 2.6.

For n=ap+b=a(k)pk+b(k)𝑛𝑎𝑝𝑏subscript𝑎𝑘superscript𝑝𝑘subscript𝑏𝑘n=ap+b=a_{(k)}p^{k}+b_{(k)} with 0b(k)pk10subscript𝑏𝑘superscript𝑝𝑘10\leq b_{(k)}\leq p^{k}-1 and defining (1kl1𝑘𝑙1\leq k\leq l and 0iak0𝑖subscript𝑎𝑘0\leq i\leq a_{k})

qa,l,k,i=(a(k)pk+b(k)ipk)!a0!(a1p)!((aki)pk)!(alpl)!subscript𝑞𝑎𝑙𝑘𝑖subscript𝑎𝑘superscript𝑝𝑘subscript𝑏𝑘𝑖superscript𝑝𝑘subscript𝑎0subscript𝑎1𝑝subscript𝑎𝑘𝑖superscript𝑝𝑘subscript𝑎𝑙superscript𝑝𝑙q_{a,l,k,i}=\frac{(a_{(k)}p^{k}+b_{(k)}-ip^{k})!}{a_{0}!(a_{1}p)!\ldots((a_{k}-i)p^{k})!\ldots(a_{l}p^{l})!}

with ak1subscript𝑎𝑘1a_{k}\geq 1, (where it is understood that when a𝑎a and l𝑙l appears together as the two first labels of one qsubscript𝑞q_{\cdot\cdot\cdot\cdot}, it implies that a𝑎a is given by a=a(1)=(a1a2al)p=a1+a2p++alpl1𝑎subscript𝑎1subscriptsubscript𝑎1subscript𝑎2subscript𝑎𝑙𝑝subscript𝑎1subscript𝑎2𝑝subscript𝑎𝑙superscript𝑝𝑙1a=a_{(1)}=(a_{1}a_{2}\ldots a_{l})_{p}=a_{1}+a_{2}p+\ldots+a_{l}p^{l-1}) we have (0i<ak0𝑖subscript𝑎𝑘0\leq i<a_{k})

(a(k)pk+b(k)ipkpk)=qa,l,k,iqa,l,k,i+1((aki)pkpk)binomialsubscript𝑎𝑘superscript𝑝𝑘subscript𝑏𝑘𝑖superscript𝑝𝑘superscript𝑝𝑘subscript𝑞𝑎𝑙𝑘𝑖subscript𝑞𝑎𝑙𝑘𝑖1binomialsubscript𝑎𝑘𝑖superscript𝑝𝑘superscript𝑝𝑘{a_{(k)}p^{k}+b_{(k)}-ip^{k}\choose p^{k}}=\frac{q_{a,l,k,i}}{q_{a,l,k,i+1}}{(a_{k}-i)p^{k}\choose p^{k}}

Additionally, qa,l,k,iqa,l,k,i+1(modp)subscript𝑞𝑎𝑙𝑘𝑖subscript𝑞𝑎𝑙𝑘𝑖1mod𝑝q_{a,l,k,i}\equiv q_{a,l,k,i+1}~{}(\textup{mod}~{}p).

In particular for k=0𝑘0k=0, we have (0i<a0)0𝑖subscript𝑎0(0\leq i<a_{0}),

ap+b=qa,l,0,iqa,l,0,i+1(a0i)𝑎𝑝𝑏subscript𝑞𝑎𝑙0𝑖subscript𝑞𝑎𝑙0𝑖1subscript𝑎0𝑖ap+b=\frac{q_{a,l,0,i}}{q_{a,l,0,i+1}}(a_{0}-i)

with a01subscript𝑎01a_{0}\geq 1.

We can prove this lemma by the following a similar reasoning as earlier and hence we omit it here.

Notice that q=qa,l,k,0𝑞subscript𝑞𝑎𝑙𝑘0q=q_{a,l,k,0}. And qa,l,k,aksubscript𝑞𝑎𝑙𝑘subscript𝑎𝑘q_{a,l,k,a_{k}} corresponds to the case where ak=0subscript𝑎𝑘0a_{k}=0. Also

qai,l,k,0=qa,l,1,iqa,l,1,i+1(modp),subscript𝑞𝑎𝑖𝑙𝑘0subscript𝑞𝑎𝑙1𝑖subscript𝑞𝑎𝑙1𝑖1mod𝑝q_{a-i,l,k,0}=q_{a,l,1,i}\equiv q_{a,l,1,i+1}~{}(\textup{mod}~{}p),

with 0i<a10𝑖subscript𝑎10\leq i<a_{1} and a11subscript𝑎11a_{1}\geq 1. So, since qa,l,k,jqa,l,k,j+1(modp)subscript𝑞𝑎𝑙𝑘𝑗subscript𝑞𝑎𝑙𝑘𝑗1mod𝑝q_{a,l,k,j}\equiv q_{a,l,k,j+1}~{}(\textup{mod}~{}p) with 0j<ak0𝑗subscript𝑎𝑘0\leq j<a_{k}, we have qai,l,k,jqai,l,k,0qa,l,1,iqa,l,1,0(modp)subscript𝑞𝑎𝑖𝑙𝑘𝑗subscript𝑞𝑎𝑖𝑙𝑘0subscript𝑞𝑎𝑙1𝑖subscript𝑞𝑎𝑙10mod𝑝q_{a-i,l,k,j}\equiv q_{a-i,l,k,0}\equiv q_{a,l,1,i}\equiv q_{a,l,1,0}~{}(\textup{mod}~{}p) and qai,l,k,0=qai,l,l,0qai,l,l,jqai,l,l,alqai,l1,k,0(modp).subscript𝑞𝑎𝑖𝑙𝑘0subscript𝑞𝑎𝑖𝑙𝑙0subscript𝑞𝑎𝑖𝑙𝑙𝑗subscript𝑞𝑎𝑖𝑙𝑙subscript𝑎𝑙subscript𝑞𝑎𝑖𝑙1𝑘0mod𝑝q_{a-i,l,k,0}=q_{a-i,l,l,0}\equiv q_{a-i,l,l,j}\equiv q_{a-i,l,l,a_{l}}\equiv q_{a-i,l-1,k,0}~{}(\textup{mod}~{}p).

So qai,l,k,0qai,l1,k,0qai,l,k,0qai,1,1,0qa,1,1,iqa,1,1,0(modp)subscript𝑞𝑎𝑖𝑙𝑘0subscript𝑞𝑎𝑖𝑙1𝑘0subscript𝑞𝑎𝑖𝑙𝑘0subscript𝑞𝑎𝑖110subscript𝑞𝑎11𝑖subscript𝑞𝑎110mod𝑝q_{a-i,l,k,0}\equiv q_{a-i,l-1,k,0}\equiv\cdots\equiv q_{a-i,l,k,0}\equiv q_{a-i,1,1,0}\equiv q_{a,1,1,i}\equiv q_{a,1,1,0}~{}(\textup{mod}~{}p). Or qai,l,k,0=qa,l,1,iqa,l,1,0qa,l,k,0(modp)subscript𝑞𝑎𝑖𝑙𝑘0subscript𝑞𝑎𝑙1𝑖subscript𝑞𝑎𝑙10subscript𝑞𝑎𝑙𝑘0mod𝑝q_{a-i,l,k,0}=q_{a,l,1,i}\equiv q_{a,l,1,0}\equiv q_{a,l,k,0}~{}(\textup{mod}~{}p).

Finally we have q=qa,l,k,0qa,1,1,0(modp)𝑞subscript𝑞𝑎𝑙𝑘0subscript𝑞𝑎110mod𝑝q=q_{a,l,k,0}\equiv q_{a,1,1,0}~{}(\textup{mod}~{}p).

Lemma 2.7.

We have also the congruence (aipi)!ai!pai(1+p++pi1)(modp).subscript𝑎𝑖superscript𝑝𝑖subscript𝑎𝑖superscript𝑝subscript𝑎𝑖1𝑝superscript𝑝𝑖1mod𝑝(a_{i}p^{i})!\equiv a_{i}!p^{a_{i}(1+p+\ldots+p^{i-1})}~{}(\textup{mod}~{}p).

Proof.

We proceed by induction on i𝑖i.

Indeed, we have (a1p)!1p2p(a11)pa1p(modp)subscript𝑎1𝑝1𝑝2𝑝subscript𝑎11𝑝subscript𝑎1𝑝mod𝑝(a_{1}p)!\equiv 1p\cdot 2p\cdots(a_{1}-1)p\cdot a_{1}p~{}(\textup{mod}~{}p). So (a1p)!a1!pa1(modp)subscript𝑎1𝑝subscript𝑎1superscript𝑝subscript𝑎1mod𝑝(a_{1}p)!\equiv a_{1}!p^{a_{1}}~{}(\textup{mod}~{}p).

It follows that (a2p2)!=((a2p)p)!(a2p)!pa2pa2!pa2pa2p(modp)subscript𝑎2superscript𝑝2subscript𝑎2𝑝𝑝subscript𝑎2𝑝superscript𝑝subscript𝑎2𝑝subscript𝑎2superscript𝑝subscript𝑎2superscript𝑝subscript𝑎2𝑝mod𝑝(a_{2}p^{2})!=((a_{2}p)p)!\equiv(a_{2}p)!p^{a_{2}p}\equiv a_{2}!p^{a_{2}}p^{a_{2}p}~{}(\textup{mod}~{}p). So (a2p2)!a2!pa2(1+p)(modp)subscript𝑎2superscript𝑝2subscript𝑎2superscript𝑝subscript𝑎21𝑝mod𝑝(a_{2}p^{2})!\equiv a_{2}!p^{a_{2}(1+p)}~{}(\textup{mod}~{}p).

Let us assume that (aipi)!ai!pai(1+p++pi1)(modp)subscript𝑎𝑖superscript𝑝𝑖subscript𝑎𝑖superscript𝑝subscript𝑎𝑖1𝑝superscript𝑝𝑖1mod𝑝(a_{i}p^{i})!\equiv a_{i}!p^{a_{i}(1+p+\ldots+p^{i-1})}~{}(\textup{mod}~{}p).

We have (ai+1pi+1)!=((ai+1pi)p)!(ai+1pi)!pai+1piai+1!pai+1(1+p++pi1)pai+1pi(modp)subscript𝑎𝑖1superscript𝑝𝑖1subscript𝑎𝑖1superscript𝑝𝑖𝑝subscript𝑎𝑖1superscript𝑝𝑖superscript𝑝subscript𝑎𝑖1superscript𝑝𝑖subscript𝑎𝑖1superscript𝑝subscript𝑎𝑖11𝑝superscript𝑝𝑖1superscript𝑝subscript𝑎𝑖1superscript𝑝𝑖mod𝑝(a_{i+1}p^{i+1})!=((a_{i+1}p^{i})p)!\equiv(a_{i+1}p^{i})!p^{a_{i+1}p^{i}}\equiv a_{i+1}!p^{a_{i+1}(1+p+\ldots+p^{i-1})}p^{a_{i+1}p^{i}}~{}(\textup{mod}~{}p). Thus (ai+1pi+1)!ai+1!pai+1(1+p++pi1+pi)(modp)subscript𝑎𝑖1superscript𝑝𝑖1subscript𝑎𝑖1superscript𝑝subscript𝑎𝑖11𝑝superscript𝑝𝑖1superscript𝑝𝑖mod𝑝(a_{i+1}p^{i+1})!\equiv a_{i+1}!p^{a_{i+1}(1+p+\ldots+p^{i-1}+p^{i})}~{}(\textup{mod}~{}p).

Hence the result follows. ∎

We now prove Theorem 2.3.

Proof.

If ai=0subscript𝑎𝑖0a_{i}=0 for i[[1,l]]𝑖delimited-[]1𝑙i\in[[1,l]], then n=a0𝑛subscript𝑎0n=a_{0} and we have n!=qa0!𝑛𝑞subscript𝑎0n!=qa_{0}! with q=1𝑞1q=1. So, if ai=0subscript𝑎𝑖0a_{i}=0 for i[[1,l]]𝑖delimited-[]1𝑙i\in[[1,l]], q1(modp)𝑞1mod𝑝q\equiv 1~{}(\textup{mod}~{}p).

Let consider the case where ai=0subscript𝑎𝑖0a_{i}=0 for all i>1𝑖1i>1, then n=a0+a1p𝑛subscript𝑎0subscript𝑎1𝑝n=a_{0}+a_{1}p and we have n!=qa0!(a1p)!𝑛𝑞subscript𝑎0subscript𝑎1𝑝n!=qa_{0}!(a_{1}p)!. Then

qa0!=n!(a1p)!=(a0+a1p)(a0+a1p1)(a1p+1)=r=0a01(a1p+a0r).𝑞subscript𝑎0𝑛subscript𝑎1𝑝subscript𝑎0subscript𝑎1𝑝subscript𝑎0subscript𝑎1𝑝1subscript𝑎1𝑝1subscriptsuperscriptproductsubscript𝑎01𝑟0subscript𝑎1𝑝subscript𝑎0𝑟qa_{0}!=\frac{n!}{(a_{1}p)!}=(a_{0}+a_{1}p)(a_{0}+a_{1}p-1)\ldots(a_{1}p+1)={\displaystyle\prod^{a_{0}-1}_{r=0}(a_{1}p+a_{0}-r)}.

Since 0<a0ra00subscript𝑎0𝑟subscript𝑎00<a_{0}-r\leq a_{0} for r[[0,a01]]𝑟delimited-[]0subscript𝑎01r\in[[0,a_{0}-1]], we obtain

qa0!r=0a01(a0r)r=1a0ra0!(modp).𝑞subscript𝑎0subscriptsuperscriptproductsubscript𝑎01𝑟0subscript𝑎0𝑟subscriptsuperscriptproductsubscript𝑎0𝑟1𝑟subscript𝑎0mod𝑝qa_{0}!\equiv{\displaystyle\prod^{a_{0}-1}_{r=0}(a_{0}-r)}\equiv{\displaystyle\prod^{a_{0}}_{r=1}r}\equiv a_{0}!~{}(\textup{mod}~{}p).

Since a0!subscript𝑎0a_{0}! and p𝑝p are relatively prime, we have q1(modp)𝑞1mod𝑝q\equiv 1~{}(\textup{mod}~{}p).

Since q=qa,l,k,0qa,l,1,0(modp)𝑞subscript𝑞𝑎𝑙𝑘0subscript𝑞𝑎𝑙10mod𝑝q=q_{a,l,k,0}\equiv q_{a,l,1,0}~{}(\textup{mod}~{}p), we conclude that q1(modp)𝑞1mod𝑝q\equiv 1~{}(\textup{mod}~{}p) whatever n𝑛n is. ∎

We come back to the proof of Theorem 1.1.

Proof.

Let m,n𝑚𝑛m,n be two positive integers whose base p𝑝p expansion with p𝑝p a prime, are

m=a0+a1p++akpk,𝑚subscript𝑎0subscript𝑎1𝑝subscript𝑎𝑘superscript𝑝𝑘m=a_{0}+a_{1}p+\ldots+a_{k}p^{k},

and

n=b0+b1p++blpl,𝑛subscript𝑏0subscript𝑏1𝑝subscript𝑏𝑙superscript𝑝𝑙n=b_{0}+b_{1}p+\ldots+b_{l}p^{l},

such that mn𝑚𝑛m\geq n. We assume that aibisubscript𝑎𝑖subscript𝑏𝑖a_{i}\geq b_{i} with i=0,1,2,,max(k,l)𝑖012𝑘𝑙i=0,1,2,\ldots,\max(k,l). We denote a=mp𝑎𝑚𝑝a=\lfloor\frac{m}{p}\rfloor and b=np𝑏𝑛𝑝b=\lfloor\frac{n}{p}\rfloor. Since aibisubscript𝑎𝑖subscript𝑏𝑖a_{i}\geq b_{i} with i=0,1,2,,max(k,l)𝑖012𝑘𝑙i=0,1,2,\ldots,\max(k,l), we have ab𝑎𝑏a\geq b. We define

amax(k,l)={0ifk<lakifklsubscript𝑎𝑘𝑙cases0if𝑘𝑙subscript𝑎𝑘if𝑘𝑙a_{\max(k,l)}=\left\{\begin{array}[]{ccc}0&{\rm if}&k<l\\ a_{k}&{\rm if}&k\geq l\end{array}\right.

and

bmax(k,l)={blifkl0ifk>lsubscript𝑏𝑘𝑙casessubscript𝑏𝑙if𝑘𝑙0if𝑘𝑙b_{\max(k,l)}=\left\{\begin{array}[]{ccc}b_{l}&{\rm if}&k\leq l\\ 0&{\rm if}&k>l\end{array}\right.

In particular if max(k,l)=k𝑘𝑙𝑘\max(k,l)=k, bi=0subscript𝑏𝑖0b_{i}=0 for i>l𝑖𝑙i>l and if max(k,l)=l𝑘𝑙𝑙\max(k,l)=l, ai=0subscript𝑎𝑖0a_{i}=0 for i>k𝑖𝑘i>k. Since mn𝑚𝑛m\geq n, max(k,l)=k𝑘𝑙𝑘\max(k,l)=k. So, we have amax(k,l)=aksubscript𝑎𝑘𝑙subscript𝑎𝑘a_{\max(k,l)}=a_{k} and bmax(k,l)=bksubscript𝑏𝑘𝑙subscript𝑏𝑘b_{\max(k,l)}=b_{k} with bk=0subscript𝑏𝑘0b_{k}=0 when l<k𝑙𝑘l<k.

Using these

m!=qa,k,1,0a0!(a1p)!(akpk)!,𝑚subscript𝑞𝑎𝑘10subscript𝑎0subscript𝑎1𝑝subscript𝑎𝑘superscript𝑝𝑘m!=q_{a,k,1,0}a_{0}!(a_{1}p)!\ldots(a_{k}p^{k})!,
n!=qb,l,1,0b0!(b1p)!(blpl)!,𝑛subscript𝑞𝑏𝑙10subscript𝑏0subscript𝑏1𝑝subscript𝑏𝑙superscript𝑝𝑙n!=q_{b,l,1,0}b_{0}!(b_{1}p)!\ldots(b_{l}p^{l})!,

and

(mn)!=qab,k,1,0(a0b0)!((a1b1)p)!((akbk)pk)!.𝑚𝑛subscript𝑞𝑎𝑏𝑘10subscript𝑎0subscript𝑏0subscript𝑎1subscript𝑏1𝑝subscript𝑎𝑘subscript𝑏𝑘superscript𝑝𝑘(m-n)!=q_{a-b,k,1,0}(a_{0}-b_{0})!((a_{1}-b_{1})p)!\ldots((a_{k}-b_{k})p^{k})!.

We have

(mn)=qa,k,1,0qb,l,1,0qab,k,1,0(a0b0)(a1pb1p)(amax(k,l)pmax(k,l)bmax(k,l)pmax(k,l)).binomial𝑚𝑛subscript𝑞𝑎𝑘10subscript𝑞𝑏𝑙10subscript𝑞𝑎𝑏𝑘10binomialsubscript𝑎0subscript𝑏0binomialsubscript𝑎1𝑝subscript𝑏1𝑝binomialsubscript𝑎𝑘𝑙superscript𝑝𝑘𝑙subscript𝑏𝑘𝑙superscript𝑝𝑘𝑙{m\choose n}=\frac{q_{a,k,1,0}}{q_{b,l,1,0}q_{a-b,k,1,0}}{a_{0}\choose b_{0}}{a_{1}p\choose b_{1}p}\ldots{a_{\max(k,l)}p^{\max(k,l)}\choose b_{\max(k,l)}p^{\max(k,l)}}.

Rearranging

qb,l,1,0qab,k,1,0(mn)=qa,k,1,0(a0b0)(a1pb1p)(amax(k,l)pmax(k,l)bmax(k,l)pmax(k,l)).subscript𝑞𝑏𝑙10subscript𝑞𝑎𝑏𝑘10binomial𝑚𝑛subscript𝑞𝑎𝑘10binomialsubscript𝑎0subscript𝑏0binomialsubscript𝑎1𝑝subscript𝑏1𝑝binomialsubscript𝑎𝑘𝑙superscript𝑝𝑘𝑙subscript𝑏𝑘𝑙superscript𝑝𝑘𝑙q_{b,l,1,0}q_{a-b,k,1,0}{m\choose n}=q_{a,k,1,0}{a_{0}\choose b_{0}}{a_{1}p\choose b_{1}p}\ldots{a_{\max(k,l)}p^{\max(k,l)}\choose b_{\max(k,l)}p^{\max(k,l)}}.

Since qa,k,1,0qb,l,1,0qab,k,1,01(modp)subscript𝑞𝑎𝑘10subscript𝑞𝑏𝑙10subscript𝑞𝑎𝑏𝑘101mod𝑝q_{a,k,1,0}\equiv q_{b,l,1,0}\equiv q_{a-b,k,1,0}\equiv 1~{}(\textup{mod}~{}p), we get

(mn)(a0b0)(a1pb1p)(amax(k,l)pmax(k,l)bmax(k,l)pmax(k,l))(modp).binomial𝑚𝑛binomialsubscript𝑎0subscript𝑏0binomialsubscript𝑎1𝑝subscript𝑏1𝑝binomialsubscript𝑎𝑘𝑙superscript𝑝𝑘𝑙subscript𝑏𝑘𝑙superscript𝑝𝑘𝑙mod𝑝{m\choose n}\equiv{a_{0}\choose b_{0}}{a_{1}p\choose b_{1}p}\ldots{a_{\max(k,l)}p^{\max(k,l)}\choose b_{\max(k,l)}p^{\max(k,l)}}~{}(\textup{mod}~{}p).

Notice that if for some i𝑖i, ai=0subscript𝑎𝑖0a_{i}=0, then bi=0subscript𝑏𝑖0b_{i}=0 since we assume that aibisubscript𝑎𝑖subscript𝑏𝑖a_{i}\geq b_{i} and bi0subscript𝑏𝑖0b_{i}\geq 0. In such a case (aipibipi)=(aibi)=1binomialsubscript𝑎𝑖superscript𝑝𝑖subscript𝑏𝑖superscript𝑝𝑖binomialsubscript𝑎𝑖subscript𝑏𝑖1{a_{i}p^{i}\choose b_{i}p^{i}}={a_{i}\choose b_{i}}=1.

We assume that ai1subscript𝑎𝑖1a_{i}\geq 1. For k[[1,aipi1]]𝑘delimited-[]1subscript𝑎𝑖superscript𝑝𝑖1k\in[[1,a_{i}p^{i}-1]] and for i[[0,max(k,l)]]𝑖delimited-[]0𝑘𝑙i\in[[0,\max(k,l)]] with 1aipi11subscript𝑎𝑖superscript𝑝𝑖11\leq a_{i}\leq p^{i}-1, (aipik)0(modp)binomialsubscript𝑎𝑖superscript𝑝𝑖𝑘0mod𝑝{a_{i}p^{i}\choose k}\equiv 0~{}(\textup{mod}~{}p)

Therefore for ai=1subscript𝑎𝑖1a_{i}=1 we have

(1+x)pi=k=0pi(pik)xk1+xpi(modp),superscript1𝑥superscript𝑝𝑖subscriptsuperscriptsuperscript𝑝𝑖𝑘0binomialsuperscript𝑝𝑖𝑘superscript𝑥𝑘1superscript𝑥superscript𝑝𝑖mod𝑝(1+x)^{p^{i}}={\displaystyle\sum^{p^{i}}_{k=0}{p^{i}\choose k}x^{k}}\equiv 1+x^{p^{i}}~{}(\textup{mod}~{}p),

and for any ai[[1,pi1]]subscript𝑎𝑖delimited-[]1superscript𝑝𝑖1a_{i}\in[[1,p^{i}-1]]

(1+x)aipi=((1+x)pi)ai(1+xpi)ai(modp).superscript1𝑥subscript𝑎𝑖superscript𝑝𝑖superscriptsuperscript1𝑥superscript𝑝𝑖subscript𝑎𝑖superscript1superscript𝑥superscript𝑝𝑖subscript𝑎𝑖mod𝑝(1+x)^{a_{i}p^{i}}=((1+x)^{p^{i}})^{a_{i}}\equiv(1+x^{p^{i}})^{a_{i}}~{}(\textup{mod}~{}p).

Now comparing

(1+x)aipi=k=0aipi(aipik)xk,superscript1𝑥subscript𝑎𝑖superscript𝑝𝑖subscriptsuperscriptsubscript𝑎𝑖superscript𝑝𝑖𝑘0binomialsubscript𝑎𝑖superscript𝑝𝑖𝑘superscript𝑥𝑘(1+x)^{a_{i}p^{i}}={\displaystyle\sum^{a_{i}p^{i}}_{k=0}{a_{i}p^{i}\choose k}x^{k}},

and

(1+xpi)ai=l=0ai(ail)xlpisuperscript1superscript𝑥superscript𝑝𝑖subscript𝑎𝑖subscriptsuperscriptsubscript𝑎𝑖𝑙0binomialsubscript𝑎𝑖𝑙superscript𝑥𝑙superscript𝑝𝑖(1+x^{p^{i}})^{a_{i}}={\displaystyle\sum^{a_{i}}_{l=0}{a_{i}\choose l}x^{lp^{i}}}

we get by taking k=bipi𝑘subscript𝑏𝑖superscript𝑝𝑖k=b_{i}p^{i} and l=bi𝑙subscript𝑏𝑖l=b_{i},

(aipibipi)(aibi)(modp).binomialsubscript𝑎𝑖superscript𝑝𝑖subscript𝑏𝑖superscript𝑝𝑖binomialsubscript𝑎𝑖subscript𝑏𝑖mod𝑝{a_{i}p^{i}\choose b_{i}p^{i}}\equiv{a_{i}\choose b_{i}}~{}(\textup{mod}~{}p).

Finally we have

(mn)(a0b0)(a1b1)(amax(k,l)bmax(k,l))(modp).binomial𝑚𝑛binomialsubscript𝑎0subscript𝑏0binomialsubscript𝑎1subscript𝑏1binomialsubscript𝑎𝑘𝑙subscript𝑏𝑘𝑙mod𝑝{m\choose n}\equiv{a_{0}\choose b_{0}}{a_{1}\choose b_{1}}\ldots{a_{\max(k,l)}\choose b_{\max(k,l)}}~{}(\textup{mod}~{}p).

References

  • [1] E. Lucas, The´´𝑒\acute{e}orie des Fonctions Nume´´𝑒\acute{e}riques Simplement Pe´´𝑒\acute{e}riodiques, Amer. J. Math., 1 (2), 184–196; 1 (3), 197–240; 1 (4), 289–321 (1878).